1994
DOI: 10.1007/bf01499014
|View full text |Cite
|
Sign up to set email alerts
|

The developmentally handicapped witness: Competency as a function of question format.

Abstract: gratefully acknowledge their support. We would also like to thank Irene Bevc for her efforts as a research assistant on this project and several anonymous reviewers for their helpful comments on earlier drafts of this article. Correspondence concerning this article should be addressed to Nitza B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
97
3
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(108 citation statements)
references
References 23 publications
7
97
3
1
Order By: Relevance
“…This result comports with research conducted by Schmidt & Brigham (1996). 6 ' They found that during opening and closing statements, a defense attorney may capitalize on the jury's biases by using leading questions and pointing out the inconsistencies of a child's testimony. They also found that a prosecuting attorney may unknowingly destroy the accuracy of a child's testimony by asking leading questions, which would only confirm the jury's biases.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This result comports with research conducted by Schmidt & Brigham (1996). 6 ' They found that during opening and closing statements, a defense attorney may capitalize on the jury's biases by using leading questions and pointing out the inconsistencies of a child's testimony. They also found that a prosecuting attorney may unknowingly destroy the accuracy of a child's testimony by asking leading questions, which would only confirm the jury's biases.…”
Section: Discussionsupporting
confidence: 81%
“…For example, the susceptibility of suggestion is reduced when child witnesses with mental retardation are asked general, openended questions 6 and questions pertaining to central actions in an event. 7 Suggestibility may also vary in more stressful situations and when questions are repeated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, Dent [11] found that ''general questions (as opposed to closed questions) prompt the most accuracy in recall for ID children''. Furthermore, Perlman [12] evaluated the developmentally handicapped (DH) versus non-handicapped individuals in regards to their competency to act as a witness ''as a function of question format''. She found that in response to general questions and free recall, individuals with DH ''did not provide as complete responses as did non-handicapped participants, although the information provided by both groups tended to be quite accurate; both groups, and particularly the DH group, were less accurate in responding to more focused short answer recall questions; DH participants had greater difficulty with misleading recall questions and false-leading specific and statement questions''.…”
Section: Introductionmentioning
confidence: 99%